Debt and financial performance of REITs in Malaysia: an optimal debt threshold analysis - Zalina Zainudin,; Izani Ibrahim,; Hafezali Iqbal Hussain,; Abdul Razak Abdul Hadi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study is to estimate the optimal debt threshold of Real Estate Investment Trusts in Malaysia (MREITs). This study uses continuous sequential threshold regression approach adopted from Bai and Perron (1998; 2003) and Perron (2006) methodologies and collaborates the threshold regression by Hansen (2001; 2015) to estimate the MREITs optimal debt threshold. In this regard, although by regulation, MREITs are allowed to use debt up to 50% of their total assets, the result of this study indicates that MREITs need to maintain a debt level of between 14.33% and 21.40%, to balance the external funding needs and the optimal level of financial performance. Given the high dividend payout requirement, and the marginal tax rate of zero, if debt is chosen as the dominant approach of obtaining external financing needs, MREITs need to carefully monitor the optimal level of debt in order to maximize the shareholders return and to avoid debt overhang problem. The finding offers a useful guide to MREITs managers in strategizing their financing decision to support their external growth needs by investing in real property.